IL-15 activates mTOR and primes stress-activated gene expression leading to prolonged antitumor capacity of NK cells - Mao, Yumeng (Blood, 2016)
Treatment of hematological malignancies by adoptive transfer of activated natural killer (NK) cells is limited by poor postinfusion persistence. We compared the ability of interleukin-2 (IL-2) and IL-15 to sustain human NK-cell functions following cytokine withdrawal to model postinfusion performance. In contrast to IL-2, IL-15 mediated stronger signaling through the IL-2/15 receptor complex and provided cell function advantages. Genome-wide analysis of cytosolic and polysome-associated messenger RNA (mRNA) revealed not only cytokine-dependent differential mRNA levels and translation during cytokine activation but also that most gene expression differences were primed by IL-15 and only manifested after cytokine withdrawal. IL-15 augmented mammalian target of rapamycin (mTOR) signaling, which correlated with increased expression of genes related to cell metabolism and respiration. Consistently, mTOR inhibition abrogated IL-15–induced cell function advantages. Moreover, mTOR-independent STAT-5 signaling contributed to improved NK-cell function during cytokine activation but not following cytokine withdrawal. The superior performance of IL-15–stimulated NK cells was also observed using a clinically applicable protocol for NK-cell expansion in vitro and in vivo. Finally, expression of IL-15 correlated with cytolytic immune functions in patients with B-cell lymphoma and favorable clinical outcome. These findings highlight the importance of mTOR-regulated metabolic processes for immune cell functions and argue for implementation of IL-15 in adoptive NK-cell cancer therapy.